Impact of antimicrobial stewardship programme on hospitalized patients at the intensive care unit: a prospective audit and feedback study - Khdour, Maher R. (Br J Clin Pharmacol, 2018)
AIMS: Inappropriate use of antibiotics is one of the most important factors contributing to the emergence of drug resistant pathogens. The purpose of this study was to measure the clinical impact of antimicrobial stewardship programme (ASP) interventions on hospitalized patients at the Intensive care unit at Palestinian Medical Complex. METHODS: A prospective audit with intervention and feedback by ASP team within 48–72 h of antibiotic administration began in September 2015. Four months of pre‐ASP data were compared with 4 months of post‐ASP data. Data collected included clinical and demographic data; use of antimicrobials measured by defined daily doses, duration of therapy, length of stay, readmission and all‐cause mortality. RESULTS: Overall, 176 interventions were made the ASP team with an average acceptance rate of 78.4%. The most accepted interventions were dose optimization (87.0%) followed by de‐escalation based on culture results with an acceptance rate of 84.4%. ASP interventions significantly reduces antimicrobial use by 24.3% (87.3 defined daily doses/100 beds vs. 66.1 defined daily doses/100 beds P < 0.001). The median (interquartile range) of length of stay was significantly reduced post ASP [11 (3–21) vs. 7 (4–19) days; P < 0.01]. Also, the median (interquartile range) of duration of therapy was significantly reduced post‐ASP [8 (5–12) days vs. 5 (3–9); P = 0.01]. There was no significant difference in overall 30‐day mortality or readmission between the pre‐ASP and post‐ASP groups (26.9% vs. 23.9%; P = 0.1) and (26.1% vs. 24.6%; P = 0.54) respectively. CONCLUSIONS: Our prospective audit and feedback programme was associated with positive impact on antimicrobial use, duration of therapy and length of stay.